2014
DOI: 10.1002/brb3.227
|View full text |Cite
|
Sign up to set email alerts
|

The development and expression of physical nicotine dependence corresponds to structural and functional alterations in the anterior cingulate‐precuneus pathway

Abstract: IntroductionPerturbations in neural function provoked by a drug are thought to induce neural adaptations, which, in the absence of the drug, give rise to withdrawal symptoms. Previously published structural data from this study indicated that the progressive development of physical dependence is associated with increasing density of white matter tracts between the anterior cingulum bundle and the precuneus.MethodsUsing functional magnetic resonance imaging, we compared 11 smokers after 11 h of abstinence from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 45 publications
5
26
2
Order By: Relevance
“…However, these results are consistent with previous studies demonstrating that connectivity within this network is strengthened during smoking withdrawal (Cole et al, 2010;Huang et al, 2014;Sutherland et al, 2013); but also that connectivity between similar regions is attenuated among smokers compared with nonsmokers (Hong et al, 2010), and is negatively correlated with nicotine dependence (Hong et al, 2009) and likelihood of relapse (Addicott et al, 2015;Janes et al, 2010). Thus, enhanced connectivity across regions including the insula, cingulate, and striatum appears to be protective when assessed as a trait-level marker independent of abstinence state, whereas state-based increases in connectivity strength co-occur with increases in subjective craving and withdrawal (Huang et al, 2014;Sutherland et al, 2013), similar to that observed here. The present findings build upon this prior research to highlight the importance of individual differences in the effects of abstinence on connectivity strength and suggest that withdrawal-induced modulation of connectivity may be associated with better cessation outcomes.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…However, these results are consistent with previous studies demonstrating that connectivity within this network is strengthened during smoking withdrawal (Cole et al, 2010;Huang et al, 2014;Sutherland et al, 2013); but also that connectivity between similar regions is attenuated among smokers compared with nonsmokers (Hong et al, 2010), and is negatively correlated with nicotine dependence (Hong et al, 2009) and likelihood of relapse (Addicott et al, 2015;Janes et al, 2010). Thus, enhanced connectivity across regions including the insula, cingulate, and striatum appears to be protective when assessed as a trait-level marker independent of abstinence state, whereas state-based increases in connectivity strength co-occur with increases in subjective craving and withdrawal (Huang et al, 2014;Sutherland et al, 2013), similar to that observed here. The present findings build upon this prior research to highlight the importance of individual differences in the effects of abstinence on connectivity strength and suggest that withdrawal-induced modulation of connectivity may be associated with better cessation outcomes.…”
Section: Discussionsupporting
confidence: 94%
“…If increased VS connectivity with the cingulo-insular network reflects a stronger degree of cognitive control over motivationally relevant stimuli, thereby enhancing the ability to inhibit the impulse to smoke, then it is somewhat surprising that such regulatory pathways were increased during abstinence among non-lapsers, particularly as tobacco withdrawal is associated with diminished ability to resist smoking (Roche et al, 2014). However, these results are consistent with previous studies demonstrating that connectivity within this network is strengthened during smoking withdrawal (Cole et al, 2010;Huang et al, 2014;Sutherland et al, 2013); but also that connectivity between similar regions is attenuated among smokers compared with nonsmokers (Hong et al, 2010), and is negatively correlated with nicotine dependence (Hong et al, 2009) and likelihood of relapse (Addicott et al, 2015;Janes et al, 2010). Thus, enhanced connectivity across regions including the insula, cingulate, and striatum appears to be protective when assessed as a trait-level marker independent of abstinence state, whereas state-based increases in connectivity strength co-occur with increases in subjective craving and withdrawal (Huang et al, 2014;Sutherland et al, 2013), similar to that observed here.…”
Section: Discussionsupporting
confidence: 86%
“…For instance, stronger dACC-precuneus structural and functional interactions are associated with greater nicotine physical dependence (Huang et al, 2013, 2014) and such functional dACC-precuneus interactions increase during withdrawal (Huang et al, 2014). As the dACC and precuneus are primary nodes of the SN and DMN respectively, the work of Haung et al is consistent with the finding that SN-DMN interactions also increase during withdrawal (Lerman et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…rsFC in many of these areas is affected by nicotine in humans, such as the anterior cingulate cortex, insula, caudate, putamen, and the prefrontal cortex. 12,13 The site exhibiting functional connectivity alterations with the widest number of other regions is the interpeduncular nucleus. Interestingly, this brain region reportedly plays a key role in nicotine withdrawal symptoms (reviewed in Dani et al 14 …”
Section: Discussionmentioning
confidence: 99%